Social Media Etiquette for the Modern Medical Student:A Narrative Review - Brittany Harrison; Jeewanjit Gill; Alireza Jalali (University Library System, University of Pittsburgh, 2014)
Most medical students worldwide are using some form of social media platform to supplement their learning via file sharing and to stay up-to-date on medical events. Often, social media may blur the line between socialization and educational use, so it is important to be aware of how one is utilizing social media and how to remain professional. Research has yielded some troublesome themes of misconduct: drunken behaviour, violations of confidentiality and defamation of institutions. Because there is no universal policy to monitor online professionalism, there exists the potential for indiscretions to occur. It has been reported that misdemeanours can affect future residency placements and employment for medical students. Accordingly, studies suggest that educators need to recognize this new era of professionalism and adapt policies and reprimands to meet modern outlets where professionalism may be violated.